2014
DOI: 10.3109/0142159x.2014.923563
|View full text |Cite
|
Sign up to set email alerts
|

Using the Knowledge, Process, Practice (KPP) model for driving the design and development of online postgraduate medical education

Abstract: The KPP model is based on best practice educational design using a structure that can be adapted for a variety of online or flexibly delivered postgraduate medical education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our study population was composed of senior dermatology residents and certified dermatologists and was comparable with the population of dermoscopy users described previously 7,8 with most women (88%) working in the private practice setting. e-Learning is undoubtedly becoming popular in the continuing medical education setting, 28 but even if e-learning is well appreciated by participants, the efficacy of e-learning modules must be rigorously evaluated compared with a conventional in-class lecture. 29 Most studies evaluating e-learning programs show important user satisfaction, but few studies show real increases in performances.…”
Section: Christmas Vacationmentioning
confidence: 99%
“…Our study population was composed of senior dermatology residents and certified dermatologists and was comparable with the population of dermoscopy users described previously 7,8 with most women (88%) working in the private practice setting. e-Learning is undoubtedly becoming popular in the continuing medical education setting, 28 but even if e-learning is well appreciated by participants, the efficacy of e-learning modules must be rigorously evaluated compared with a conventional in-class lecture. 29 Most studies evaluating e-learning programs show important user satisfaction, but few studies show real increases in performances.…”
Section: Christmas Vacationmentioning
confidence: 99%
“…Physicians in training are required to demonstrate skills and knowledge across an increasingly large number of competencies while developing skills in their chosen discipline [ 11 , 12 ]. Even though adult learning principles have long identified that education and training must be contextually relevant and directly linked to practice [ 13 ], many safety and quality programs in hospitals are delivered via didactic lectures or workshops that are not specific to the training environment or practice [ 14 ]. While online learning is increasingly employed for the scalable delivery of education to doctors in training, there is little evidence in the literature regarding whether computer-based online educational methodologies are effective in actually changing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 42 out of 51 states'/territories' licensing boards require completion of 16 to 150 CME hours annually, biennially, or triennially (Federation of State Medical Boards, 2018). However, with the rapid development of web-based CME interventions, fundamental health communication and education design principles are potentially disregarded limiting program quality and efficacy, such as lack of impact on clinicians' knowledge and practice and limited improvement in quality patient care (Goldberg & McKhann, 2000;Harris, Novalis-Marine, & Harris, 2003;Shaw, Barnet, Mcgregor, & Avery, 2015). Therefore, public health and medical officials are potentially unaware of whether these web-based interventions and programs are achieving their intended outcomes, and which components need revisions and improvements (Kreps, 2002;Kreps, 2012).…”
Section: Introductionmentioning
confidence: 99%